The impact of postharvest storage and cooking time on mineral bioaccessibility in common beans. Issue 9 (21st August 2020) - Rousseau, Sofie; Celus, Miete; Duijsens, Dorine; Gwala, Shannon; Hendrickx, Marc; Grauwet, Tara
Abstract : Postharvest storage negatively influences the common bean mineral bioaccessibility which cannot be counteracted by adapting conventional processing variables. However, dehulling can lead to an improvement of mineral bioaccessibility. Abstract : Mineral (Mg, Ca, Fe and Zn) bioaccessibility in common beans was evaluated taking into consideration the common bean food chain from postharvest storage over processing (soaking and cooking) until consumption. Beans were stored under realistic tropical conditions (35 °C and 80% RH) which resulted in significantly different cooking behaviour after 8 weeks compared to freshly harvested beans. Based on postcooking hardness, different storage times were selected: unstored, 8 and 20 weeks. Independently of storage conditions, beans were soaked overnight and cooked for 30, 60 or 120 min. The mineral bioaccessibility decreased with increase in both storage and cooking times. Decrease in mineral bioaccessibility with increasing storage time was proved to be the result of increasing mineral chelation of cell wall polymers ( e.g. pectin). Additionally, we hypothesize that by cooking, mineral chelators become more accessible, e.g. through pectin solubilization phenomena, in turn capturing more free minerals leading to a reduced mineral bioaccessibility.